The Influence of Ownership Structure, Asset Structure, and Earning Volatility on Debt Policy in Indonesia - Saiful Anwar (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
The higher the proportion of debt, the higher the stock price, but at a certain point, the increase in debt will reduce the value of the company because the benefits obtained from the use of debt are smaller than the costs incurred. The purpose of this study is to analyze the influence of ownership structure – managerial ownership and institutional ownership, asset structure, and earning volatility on debt policy. The data used in this study are secondary data in the form of managerial ownership data, institutional ownership, asset structure, earning volatility and debt policy in pharmaceutical companies that go public on the Indonesia Stock Exchange 2013-2017. The statistical method used is the Stepwise Regression, because there is high multicollinearity in managerial ownership variables, institutional ownership, assets structure, earning volatility. Based on the results of the Stepwise Regression shows that the variables entered into the regression model are earning volatility. Other variables such as managerial ownership, institutional ownership, asset structures are not included in the Stepwise Regression so that conclusion is only earning volatility variable that influences the debt policy earning volatility variables that affect debt policy.